2016
DOI: 10.1007/s12022-016-9460-5
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and Genetic Characterization of Bilateral Adrenomedullary Hyperplasia in a Patient with Germline MAX Mutation

Abstract: Background: In recent years, familial pheochromocytoma (PHEO) with germline mutations in the MAX (MYC Associated Factor X) gene has been reported in a few cases. Here we investigated a 25 years old patient with multiple PHEOs associated with a non-sense germline MAX mutation. Preoperative 18F-FDOPA PET/CT revealed bilateral adrenal involvement with multiple tumors. In addition both adrenal glands were found to have diffuse or nodular adrenal medullary hyperplasia (AMH), a histopathological feature previously d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 14 publications
(19 reference statements)
1
12
1
Order By: Relevance
“…However, Romanet et al found that there still existed a wild-type allele in the MAX-mutated PCC. And they thought that for MAX-mutated tumors, in addition to chromosomal loss and uniparental disomy, other potential mechanisms can account for the loss of MAX protein expression (8). In the present case, we found that the parents of the proband did not have MAX variants, which suggested that the germline MAX variants of the proband were de novo.…”
Section: Discussionsupporting
confidence: 50%
“…However, Romanet et al found that there still existed a wild-type allele in the MAX-mutated PCC. And they thought that for MAX-mutated tumors, in addition to chromosomal loss and uniparental disomy, other potential mechanisms can account for the loss of MAX protein expression (8). In the present case, we found that the parents of the proband did not have MAX variants, which suggested that the germline MAX variants of the proband were de novo.…”
Section: Discussionsupporting
confidence: 50%
“…Up to now, roughly 60 patients with MAX mutations have been reported in the literature. For a detailed list of cases of MAX variants reported in the literature, please refer to Supplementary Table 2 (Comino-Mendez et al 2011, Burnichon et al 2012, Peczkowska et al 2013, Welander et al 2014, Bausch et al 2017, Romanet et al 2017.…”
Section: Myc Associated Factor X (Max)mentioning
confidence: 99%
“…Moreover, a 25-years-old patient with multiple PCCs associated with adrenal medullary hyperplasia and with a nonsense germline MAX mutation was described (56).…”
Section: Discussionmentioning
confidence: 99%